Optimal selection of location, sizing and power factor for solar PV plants using differential evolution - Dang Huy P.; Ramachandaramurthy V.K.; Pesaran H.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Distributed power generation; Electric power factor; Electric power systems; Evolutionary algorithms; Fossil fuel power plants; Fossil fuels; Location; Optimization; Photovoltaic cells; Smart power grids; Solar energy; Solar power generation; Differential Evolution; Differential evolution method; Environmental concerns; Optimal selection; Power distributions; Power system constraints; Renewable energies; Technical loss; Electric power transmission networks